Adipose Stromal Cell-Secretome Counteracts Profibrotic Signals From IPF Lung Matrices - Vasse, Gwenda F.; Van Os, Lisette; De Jager, Marina; Jonker, Marnix R.; Borghuis, Theo; Van Den Toorn, L. Tim; Jellema, Pytrick; White, Eric S.; Van Rijn, Patrick; Harmsen, Martin C.; Heijink, Irene H.; Melgert, Barbro N.; et al. (Frontiers in Pharmacology, 2021)
Introduction Idiopathic pulmonary fibrosis (IPF) is a fibrotic lung disease characterized by excess deposition and altered structure of extracellular matrix (ECM) in the lungs. The fibrotic ECM is paramount in directing resident cells towards a profibrotic phenotype. Collagens, an important part of the fibrotic ECM, have been shown to be structurally different in IPF. To further understand the disease to develop better treatments, the signals from the ECM that drive fibrosis need to be identified. Adipose tissue-derived stromal cell conditioned medium (ASC-CM) has demonstrated antifibrotic effects in animal studies but has not been tested in human samples yet. In this study, the collagen structural integrity in (fibrotic) lung tissue, its interactions with fibroblasts and effects of ASC-CM treatment hereon were studied. Methods Native and decellularized lung tissue from patients with IPF and controls were stained for denatured collagen using a collagen hybridizing peptide. Primary lung fibroblasts were seeded into decellularized matrices from IPF and control subjects and cultured for 7 days in the presence or absence of ASC-CM. Reseeded matrices were fixed, stained and analyzed for total tissue deposition and specific protein expression. Results In both native and decellularized lung tissue, more denatured collagen was observed in IPF tissue compared to control tissue. Upon recellularization with fibroblasts, the presence of denatured collagen was equalized in IPF and control matrices, whereas total ECM was higher in IPF matrices than in the control. Treatment with ASC-CM resulted in less ECM deposition, but did not alter the levels of denatured collagen. Discussion Our data showed that ASC-CM can inhibit fibrotic ECM-induced profibrotic behavior of fibroblasts. This process was independent of collagen structural integrity. Our findings open up new avenues for ASC-CM to be explored as treatment for IPF.